Spatial segregation of families with migrant background in the high-status City of Munich: How strong is the effect of socio-economic status? - Hanslmaier, Michael; Teltemann, Janna; Windzio, Michael (Frontiers in Sociology, 2023)
Ethnic residential segregation can result from preferential choices or from market forces. Depending on whether it evolved voluntarily or forcibly, segregation can have differential effects on immigrant integration. Using the example of Munich as a major German city, we examine the unequal spatial distribution of migrants and non-migrants. Following Kalter (2001) we calculate indices of residential segregation, which are adjusted for differences in socio-economic status. Results show that almost 14 percent of the residential segregation of immigrants can be attributed to socio-economic restrictions. This finding suggests that factors related to immigration and, possibly, also ethnic boundaries are determinants of the unequal spatial distribution also in high-status cities such as Munich.